Pengaruh Literasi Pasar Modal Syariah, Risiko Investasi Syariah dan Motivasi Investasi Terhadap Minat Generasi Milenial dalam Berinvestasi di Pasar Modal Syariah - Dedi Hutariyani; Nur Hendrasto; Andre Herlambang (Department Islamic Economics, 2023)
Based on the formulation of the problem that has been presented, the objectives of conducting this research are: (1) To analyze the influence of the Islamic Capital Market Literacy variable on investment intentions, (2) to analyze the influence of the Islamic Investment Risk variable on investment intentions and (3) to analyze the influence Investment Motivation variable on investment interest. This study is quantitative research, the model analysis technique used in this study is Structural Equation Modeling (SEM). SEM allows simultaneous modeling between the independent and dependent variables being constructed. Structural equation modeling or Structural Equation Modeling (SEM) with data analysis tools through Partial Least Square (PLS). The population of this study consist of the millennial generation who live in Jabodetabek. Sampling was carried out using the minimum criteria from SEM-PLS, ranging from 35-100. Data was obtained using a questionnaire and processed using the SmartPLS 4.0 application. Islamic capital market literacy (0.28), investment motivation (0.39), and investment risk (0.37) have a significant positive effect on investment interest as can be seen in the original sample values and p- values. The significance level of each variable is indicated by the T statistics value with details; Islamic capital market literacy (3.15), investment motivation (5.76), and investment risk (4.58).